Reliability-based Assessment of the Structural Integrity of some Existing Reinforced Concrete Columns - Akingbonmire, Samuel Lambe; Afolayan, Joseph Olaseinde (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Abnormal loading can initiate the progressive collapse of a reinforced concrete building. A progressive collapse may start as a local failure, followed by a sequence of reactions leading to a massive portion failure of an entire structure. Reinforced concrete columns are significant structural elements in ascertaining the integrity of framed buildings. This paper presents the report on the structural integrity of reinforced concrete columns of two selected university buildings labelled A and B investigated by using non-destructive testing techniques. First-Order Reliability Method (FORM) was deployed to process the data from the field in order to generate the implied safety indices for all accessed columns in the two buildings. The computed safety indices decrease as the simulated designed practical axial loads/moments increase for all the assumed steel ratios (0.4%, 1.59% and 6%) based on BS 8110:1997:1. When compared with the target safety level of 3.8 according to BS EN 1990:2002+A1:2005 for 50 years reference period of Class RC2 structural members in the ultimate limit state, almost all the columns passed the reliability test except the columns labelled 71 in building A; and C81A and C85 for building B. The highlighted critical columns show the direction for immediate repairs to forestall the initiation of eventual progressive failure of the buildings.